The Effect of reflex Oxytocin Massage on Smooth Breast Milk Production in Post Sectio Caesarea (SC) in The Melati Room of Ganesha General Hospital - Endelawati, Komang Adi; Widiastini, Luh Putu; Sumawati, Ni Made Risna (Fakultas Kedokteran, 2022)
Oxytocin massage is a massage of the spine that starts at the cervical spine (cervical vertebrae) and up to the 12th thoracic spine. Oxytocin massage is a method of facilitating milk production which is done by massaging the back area along both sides of the spine to relax tension in the back and relieve stress so that it can facilitate the release of breast milk. The purpose of this study was to examine the effect of oxytocin massage on the smooth production of breast milk in post-sc mothers at Ganesha Hospital. This research used Quasy Experimental design with a nonequivalent control group design approach and with an Accidental sampling technique, the sample in this research was 30 postpartum post-SC mothers. Collecting data using questionnaires and observation sheets. Data were analyzed using analysis using the Mann-Whitney test with a confidence level of p≤0.05. The results showed a p-value <0.05 so it could be concluded that there was an effect of oxytocin massage on the smooth production of breast milk in post-sc mothers at RSU Ganesha.